(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of academic motivation among Medical Laboratory Technology students at Vinh Medical University and to identify factors associated with their academic motivation. Subjects and Methods: A cross-sectional descriptive study with analytical components was conducted from September 2025 to April 2026 among 207 Medical Laboratory Technology students from the first to the fourth academic year at Vinh Medical University. Data were collected using a self-administered questionnaire consisting of demographic characteristics, potential influencing factors, and the Academic Motivation Scale (AMS), which includes 28 items assessing seven dimensions of academic motivation. Academic motivation was evaluated using the Self-Determination Index (SDI). Data were entered and analyzed using SPSS version 20.0. Results: The proportion of students with good academic motivation was 65.3%, whereas 34.7% demonstrated suboptimal academic motivation. The mean scores of all motivation dimensions were above 4.0. Identified external regulation had the highest mean score (5.8 ± 0.9), while amotivation had the lowest mean score (1.9 ± 1.0). Factors significantly associated with academic motivation included self-confidence (OR = 2.21), support and encouragement from family and friends (OR = 2.75), positive perceptions of the image and role of the Medical Laboratory Technology profession in society (OR = 3.40), appropriate teaching methods (OR = 3.13), guidance and encouragement from lecturers (OR = 2.59), and a suitable training curriculum (OR = 3.52) (p < 0.05). Conclusion: Most Medical Laboratory Technology students at Vinh Medical University exhibited good academic motivation. Academic motivation was influenced by individual, family, professional perception, and educational environment factors. Universities should strengthen academic support services, innovate teaching methods, and continuously improve training programs to enhance students’ academic motivation.